2002
DOI: 10.1136/gut.50.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Excessive alcohol consumption favours high risk polyp or colorectal cancer occurrence among patients with adenomas: a case control study

Abstract: Background and aims: Excessive alcohol consumption is a risk factor for developing colorectal adenomas. This study aimed to investigate the influence of excessive alcohol consumption on the occurrence of high risk polyps (adenoma >10 mm, villous component, high grade dysplasia) or colorectal cancer among patients with at least one colonic adenoma. Patients and methods: Three groups of patients with at least one colorectal adenoma were included in a case control study: 401 heavy drinkers (group HD, mean daily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 36 publications
0
33
1
1
Order By: Relevance
“…Despite this fact we were able to detect an age effect in a >50 age group. Although smoking and alcohol consumption is associated with an increased risk for colorectal cancer (Bardou et al, 2002;Emmons et al, 2005) probably due to DNA damage via increased levels of oxidative stress (Lodovici and Bigagli, 2009;Obe and Anderson, 1987;Pool-Zobel et al, 2004), no statistically significant differences were found in our study when focussing on smoking habits, alcohol intake or diet. This was also the case in the IBD study (Study I).…”
Section: The Effect Of Flavonoids In Soybean Products In Lymphocytes contrasting
confidence: 47%
“…Despite this fact we were able to detect an age effect in a >50 age group. Although smoking and alcohol consumption is associated with an increased risk for colorectal cancer (Bardou et al, 2002;Emmons et al, 2005) probably due to DNA damage via increased levels of oxidative stress (Lodovici and Bigagli, 2009;Obe and Anderson, 1987;Pool-Zobel et al, 2004), no statistically significant differences were found in our study when focussing on smoking habits, alcohol intake or diet. This was also the case in the IBD study (Study I).…”
Section: The Effect Of Flavonoids In Soybean Products In Lymphocytes contrasting
confidence: 47%
“…The majority of individual casecontrol [10][11][12]39,[41][42][43][44][45] and cohort studies [14][15][16]18,25,40,[46][47][48][49] have shown rather inconsistent results, which in part can be explained by differing (methodological) aspects of these studies and lack of statistical power. To the best of our knowledge, our study is currently the largest single prospective study that has investigated associations between alcohol consumption and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of both colonic polyps and adenomas is said to be higher in the cirrhotics than in the general population due to an uncertain reason [183,184]. The prevalence of colonic polyps in cirrhotics varies from 8 to 46%.…”
Section: Colonic Polyp and Adenomamentioning
confidence: 97%